Growth, volatility and education: panel evidence from developing countries - Mhd Bani, Nor Yasmin; Kedir, Abbi Mamo (Faculty of Economics and Management, Universiti Putra Malaysia, 2017)
The investigation of the growth-volatility link is an important one in empirical macroeconomics. There is no empirical evidence supporting the predictions of recent theoretical models that incorporate and explicitly recognize the role of human capital in this link. The objective of the study is to examine whether the significance of volatility-growth relationship varies according to the average years of education. Using a panel data, we empirically show how the detrimental effect of output volatility on growth is diluted by education. The main contribution of our work is that while the level of volatility negatively affects growth, the effect is mediated via education. This is true even for countries with low as well as moderately high levels of volatility. This finding is consistent with Canton’s (2000) theoretical work. We also provide robustness checks and policy implications of our finding.